A new species of Solenidium (Orchidaceae) from Ecuador - Dalström, Stig; Whitten, W. Mark (Lankesteriana: International Journal on Orchidology, 2016)
A new species from Ecuador; Solenidium portillae (Orchidaceae: Oncidiinae) is described, com- pared with the other two accepted species in the genus, and illustrated. A brief history of the genus is pre- sented and a key to the species is provided.